2010
DOI: 10.1093/cvr/cvq213
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of Egr-1 in nicotine-related neointimal formation

Abstract: Nicotine acts through its receptors in VSMC to activate the ERK-Egr-1 signaling cascade that induces cell proliferation and exacerbates post-injury neointimal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Therefore, transcriptional activation of Egr1 and its downstream targets is pivotal in cellular events following oxidant stress. It has been reported that ERK1/2 is translocated to the nucleus of vascular smooth muscle cells after nicotine exposure to target the transcription factor ELK1, which, in turn, upregulates the expression of EGR1 as a key player in the progression of atherosclerosis . Therefore, in the present study we evaluated Egr1 expression in mice to investigate the role of the ERK/ELK1 pathway in the action of pravastatin in preventing the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, transcriptional activation of Egr1 and its downstream targets is pivotal in cellular events following oxidant stress. It has been reported that ERK1/2 is translocated to the nucleus of vascular smooth muscle cells after nicotine exposure to target the transcription factor ELK1, which, in turn, upregulates the expression of EGR1 as a key player in the progression of atherosclerosis . Therefore, in the present study we evaluated Egr1 expression in mice to investigate the role of the ERK/ELK1 pathway in the action of pravastatin in preventing the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it has been reported that activation of the ROS/ERK/ELK1 pathway upregulates early growth response 1 (EGR1), a major mediator of the cellular stress response that is induced by stress, injury, mitogens and cytokines . Furthermore, EGR1 has been consistently implicated in vascular pathology as a key regulator of cellular proliferative and apoptotic pathways, so EGR1 is a known atherogenic transcription factor . Thus, the ERK1/2/ELK1 pathway may be an important target in the treatment of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNAi Consortium lentiviruses (Thermo Scientific Open Biosystems, Huntsville, AL) carrying short hairpin (sh)RNAs to knock down murine SCF were initially tested in VSMCs. Cells were cultured and puromycin selected as previously described (45). The selected functional sequence for in vivo knockdown was 5=-TTACAAGCGAAATGAGAGCCG-3= (clone identifier: TRCN0000067868).…”
Section: Methodsmentioning
confidence: 99%
“…Its involvement has been reported in cancer metastasis [12], inflammation [13], atherosclerosis [14], and ischemic injury [15]. Moreover, recent studies revealed that abnormal expression and function of Egr-1 are linked to animal models of fibrosis, as well as human fibrotic disorders, including idiopathic pulmonary fibrosis and scleroderma [16,17,18].…”
Section: Introductionmentioning
confidence: 99%